Convergence of an algorithm for the largest singular value of a nonnegative rectangular tensor - Zhou, Guanglu; Caccetta, Louis; Qi, L. (Elsevier BV, 2013)
In this paper, we present an iterative algorithm for computing thelargest singular value of a nonnegative rectangular tensor.We establishthe convergence of this algorithm for any irreducible nonnegativerectangular tensor.